Electric field and air ion exposures near high voltage overhead power lines and adult cancers: a case control study across England and Wales - Toledano,MB; Shaddick,G; de,Hoogh C; Fecht,D; Freni,Sterrantino A; Matthews,J; Wright,M; Gulliver,J; Elliott,P (International Journal of Epidemiology, 2020)
Background: Various mechanisms have been postulated to explain how electric fields emitted by high voltage overhead power lines, and the charged ions they produce, might be associated with possible adult cancer risk but this has not previously been systematically explored in large scale epidemiologic research. Methods: We investigated risks of adult cancers in relation to modelled air ion density (per cm3) within 600m (focusing analysis on mouth, lung, respiratory) and calculated electric field within 25m (focusing analysis on non-melanoma skin) of high voltage overhead power lines in England and Wales, 1974-2008. Results: With adjustment for age, sex, deprivation and rurality, odds ratios (OR) in the highest fifth of net air ion density (0.504-1) compared with the lowest (0-0.1879) ranged from 0.94 (95% CI 0.82 – 1.08) for mouth cancers to 1.03 (95% CI 0.97 -1.09) for respiratory system cancers, with no trends in risk. The pattern of cancer risk was similar using corona ion estimates from an alternative model proposed by others. For keratinocyte carcinoma, adjusted OR in the highest (1.06 - 4.11 kV/m) compared with the lowest (<0.70 kV/m) thirds of electric field strength was 1.23 (95% CI 0.65-2.34) with no trend in risk. Conclusions: Our results do not provide evidence to support hypotheses that air ion density or electric fields in the vicinity of power lines are associated with cancer risk in adults.